The effect of freezing amniotic fluid on lamellar body count fetal lung maturity testing. Issue 2 (26th February 2017) - Carroll, Sarah; Towers, Craig V.; Wolfe, Lynlee; Duncan, Lisa; Weitz, Beth; Porter, Stephanie
Abstract : A short freeze–thaw process had little effect on the reliability of a mature lamellar body count test result.